(untitled) (Fountain Journal of Natural and Applied Sciences, 2017)
Nutrient and Antinutrient Compositions of Some Edible Insect Species in Northern Nigeria. The nutrient and antinutrient compositions of Moth caterpillar (Cirinaforda), Termite (Macrotermes nigierensis), Cricket (Gryllus assimilis) and Grasshopper (Melanoplus foedus) were determined. The proximate compositions were analysed using the methods of the Association of official Analytical Chemist while minerals were estimated using Atomic absorption spectrophotometry. The fatty acid profile of the oils extracted from the insects was determined by Gas chromatography/Mass spectrometry method. The vitamin and antinutrient composition of these insects were determined using standard laboratory methods. Termite was found to contain the highest amounts of moisture (4.50 ± 0.12%), ash (8.00 ± 0.12%) and fats (40.83 ± 0.03%) while moth caterpillar was found to have the highest amount of crude fibre and carbohydrate (13.25 ± 0.21%). Grasshopper was found to have the highest amount of crude protein (75.08 ± 0.91 %) while termite contained the least amount of protein (43.75 ± 0.03%). The Metabolisable energy of the insects were generally high and ranged from 392.83 ± 0.35 kcal/100g in grasshopper to 554.00 ± 3.40kcal/100g in termite. Potassium was the most abundant mineral in all the insects. Palmitic acid was found in high amounts in termite (25.78%), moth caterpillar (20.78%) and grasshopper (21.15%) while cricket had the lowest palmitic acid content (1.69%). The essential fatty acids found in the insects were linolenic acid and linoleic acid. Moth Caterpillar had the highest amount of linolenic acid (28.69%) while grasshopper had the highest amount of linoleic acid (17.2%). Vitamin E was found to be the most abundant vitamin while vitamin B2 was the least abundant in all the insects analysed. Antinutrients in all the insects were within permissible limits and may not pose any threat to their usage as sources of food. These results have thus justified the consumption of these insects as food. Keywords: Edible insects, Nutrients, Antinutrients, Vitamin, Mineral, Fatty acids